Asymptomatic neuroendocrine tumor of the ileocecal area in a 59 year-old patient – a case study - Wojnicka-Stolarz, Małgorzata; Gąszcz, Anna; Książek, Mariusz; Gutkowska, Dorota; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2016)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">One of the more common locations of neuroendocrine tumors (Neuroendocrine Tumors, NET) of the gastrointestinal tract is the small intestine. In the majority of cases, these are slow to develop, highly differentiated tumors, which pose a diagnostic challenge to gastroenterologists, radiologists and pathologists. From the clinical viewpoint, NETs of the small intestine may be hormonally inactive or produce substances responsible for the occurrence of characteristic clinical symptoms. The serum concentration of chromogranin A is a sensitive, yet nonspecific, marker of such changes. The basic method of diagnosing is through the use of imaging techniques, which allow for the location of the tumor; and endoscopic techniques, which permit the extraction of a tissue sample for histopathology and immunohistochemistry ancillary tests. Surgical excision of a lesion is the treatment of choice. However, if pharmacotherapy is employed, the somatostatin analogs, radioisotope therapy and chemotherapy is used. We present a case study, of an asymptomatic neuroendocrine tumor of the ileocecal area, in a 59 year-old male patient.